Microstrip technique and modeling for determination of microwave properties of Ni-Zn ferrite - Esa, Fahmiruddin (2015)
Ni-Zn ferrite has been such important topics since 1900 but the reported works are mainly discussed on the sample preparation technique also microstructural and morphological analysis. Even though microwave properties of Ni-Zn ferrite have also been discovered by various workers using waveguide technique however air gap problems are still remain as the major issues. Furthermore, the effect of different Ni-Zn ratio in NiₓZn₁˗ₓFe₂O₄ on the reflection, transmission and absorption properties in a wideband and higher frequency using microstrip technique has not been investigated. This thesis describes a detailed study on the application of a microstrip technique to determine the microwave properties of NiₓZn₁˗ₓFe₂O₄ in the frequency range between 1 GHz and 10 GHz. The x compositions of the spinel ferrite were 0.1, 0.3, 0.5, 0.7, 0.9. The NiₓZn₁˗ₓFe₂O₄ samples were prepared by 10 hours sintering at 900°C with 4°C/min increment from room temperature. Particles showed phase purity and crystallinity in powder X-ray diffraction (XRD) analysis. Surface morphology measurement of Scanning Electron Microcopy (SEM) was conducted on the plane surfaces of the molded samples which gave information about grain morphology, boundaries and porosity. The tabulated grain size for all samples was in the range of 62 nm – 175 nm. Energy dispersive X-ray analysis (EDX) was done to confirm the elemental composition of the Ni-Zn ferrite samples by their weight and atomic percentage of each element for certain particular composition taken from specific area of the micrograph. The transmission (S₂₁) and reflection (S₁₁) properties of the microstrip loaded with NiₓZn₁˗ₓFe₂O₄ were extensively studied theoretically using finite element method. The microstrip measurements were conducted using a HP8720B vector network analyzer. The electromagnetic field distribution of the microstrip covered with Ni₀.₅Zn₀.₅Fe₂O₄ sample was visualized using FEM software COMSOL. It was found that NiₓZn₁˗ₓFe₂O₄ with higher values of x absorbed more microwave energy which in turn reduced the reflection and transmission coefficients. A good linear relationship was found between the absorption loss and fractional composition x at 3 GHz. The waves were totally absorbed by NiₓZn₁˗ₓFe₂O₄ at frequencies above 7 GHz for x ≥ 0.5. An optimization routine was also introduced in this work to determine both the permittivity and permeability of Ni₀.₅Zn₀.₅Fe₂O₄ sample by matching the theoretical and measured values of S₁₁ and S₂₁. The complex permittivity and permeability of Ni₀.₅Zn₀.₅Fe₂O₄ sample along the frequency ranges were linked to the other findings. The measured S-parameters were compared with the results obtained using the Nicolson Ross Weir (NRW), Finite Element Method (FEM) and optimization method. The optimization method provides the highest accuracy when compared with the measured |S₁₁| and |S₂₁| with a mean error 0.0403 and 0.0177, respectively.